2020
DOI: 10.3390/nu12103206
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mediterranean Diet’s Adherence in Children with Inflammatory Bowel Diseases

Abstract: Background: Nutritional support is very important in the treatment of Paediatric Inflammatory Bowel Disease (IBD). The role of the Mediterranean Diet (MD) has been understudied in children with IBD. The aims of this study were to assess the dietary intakes of IBD children in comparison with healthy controls (HCs), their adherence to MD; and the relationship between inflammation and dietary behaviors. Methods: Paediatric IBD patients in clinical remission and HCs were enrolled. The nutritional status and adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Protein supplementation was captured but was not an inclusion or exclusion criteria. If subjects met criteria, they were asked to sign a consent form, at which points participants were explained in detail how to fill-out a 3-day food diary, an instrument commonly used to access food intake [17,18] and could ask any clarifying questions (3-day food diary facsimile is available as Supplementary Materials). A total of 166 participants completed the dietary journal, 125 males and 41 females.…”
Section: Methodsmentioning
confidence: 99%
“…Protein supplementation was captured but was not an inclusion or exclusion criteria. If subjects met criteria, they were asked to sign a consent form, at which points participants were explained in detail how to fill-out a 3-day food diary, an instrument commonly used to access food intake [17,18] and could ask any clarifying questions (3-day food diary facsimile is available as Supplementary Materials). A total of 166 participants completed the dietary journal, 125 males and 41 females.…”
Section: Methodsmentioning
confidence: 99%
“…Microbiome changes were variable among participants from the 2020 study by Suskind et al [ 68 ]. Some studies have identified increased microbiome diversity in CD patients on the SCD, while others have used murine models to show that carbohydrate monotony provides a selective pressure favouring certain intestinal bacterial species while decreasing the total diversity [ 106 , 108 ]. Microbial composition in all three groups (SCD, mSCD, WF) showed a trend towards increased microbial diversity (Inverse Simpson Index), from 4.67–14.09 at enrollment to 10.93–17.76 at the end of the two-week study period [ 68 ].…”
Section: Diets Without Proven Clinical Efficacy For Ibdmentioning
confidence: 99%
“…The authors concluded that the CD-TREAT diet could achieve similar effects on the microbiome as EEN in both healthy adults and experimental rat models. The report of the larger clinical trial is eagerly awaited and will hopefully add another option to the dietary treatments of CD [ 106 , 108 , 109 ].…”
Section: Diets Without Proven Clinical Efficacy For Ibdmentioning
confidence: 99%
“…Moreover, better adherence to a modified Mediterranean diet was associated with a lower risk of Crohn’s disease, although not of ulcerative colitis [ 94 ]. In fact, as research suggests, the Mediterranean diet reduced intestinal inflammation in IBD children in clinical remission [ 95 ]. It is vital to note that the results of an in vitro and in vivo study revealed that extra virgin olive oil (an important element of the MD diet) might improve disease symptoms in immune-mediated inflammatory diseases [ 96 ].…”
Section: Dietary Support Supplementation and Imaging Techniquesmentioning
confidence: 99%